2021
DOI: 10.1038/s41598-021-89311-3
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of muscle MRI: machine learning-based classifications in idiopathic inflammatory myopathies

Abstract: To develop a machine learning (ML) model that predicts disease groups or autoantibodies in patients with idiopathic inflammatory myopathies (IIMs) using muscle MRI radiomics features. Twenty-two patients with dermatomyositis (DM), 14 with amyopathic dermatomyositis (ADM), 19 with polymyositis (PM) and 19 with non-IIM were enrolled. Using 2D manual segmentation, 93 original features as well as 93 local binary pattern (LBP) features were extracted from MRI (short-tau inversion recovery [STIR] imaging) of proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…These image characteristics are based on the microstructures of a background tissue and are sometimes imperceptible to the human visual system [ 13 ]. TA has been applied to a number of medical image assessments, including oncologic imaging [ 15 , 16 ], neuroimaging [ 17 , 18 ], and musculoskeletal imaging [ 19 , 20 ]. In pelvic MRI on ovarian sex cord-stromal tumors, recent radiomics studies reported the differentiation of OTFGs from uterine fibroids in the adnexal area [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These image characteristics are based on the microstructures of a background tissue and are sometimes imperceptible to the human visual system [ 13 ]. TA has been applied to a number of medical image assessments, including oncologic imaging [ 15 , 16 ], neuroimaging [ 17 , 18 ], and musculoskeletal imaging [ 19 , 20 ]. In pelvic MRI on ovarian sex cord-stromal tumors, recent radiomics studies reported the differentiation of OTFGs from uterine fibroids in the adnexal area [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As deep-learning is now widely used for the diagnosis of various diseases, the deep-learning or convolutional neural network (CNN) method would assist in the construction of favorable classification models. The MLP is the simplest form of an artificial neural network; it simulates the nervous system properties and biological learning functions through an adaptive process ( 31 , 32 ). The present study implemented the MLP classifier and conducted the preliminary study on CNN-based classification models.…”
Section: Discussionmentioning
confidence: 99%
“…It can be a problem in statistical analysis such as regression as it distorts the prediction results of the model [27,28]. For classification-based machine learning, the multi-collinearity problem can be addressed as part of feature selection (e.g., [27,[37][38][39]). In this study, features with weak inter-correlation are candidates to be selected.…”
Section: Multi-collinearitymentioning
confidence: 99%